2018
DOI: 10.3390/met8070527
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Microstructural Heterogeneity on Mechanical Properties of Friction Stir Welded Joints of T6-Treated Al-Zn-Mg Alloy 7A52

Abstract: A high strength Al-Zn-Mg alloy 7A52 with T6 treatment was successfully friction stir welded. The grain structure, dislocations and precipitates in typical regions of the weld joint, including the weld nugget zone (WNZ), thermos-mechanically affected zones (TMAZ) and heat affected zones (HAZ) were investigated to understand the mechanical properties of each zone and the weld joint. In WNZ, a relatively higher density of dislocations is observed on the advancing side, caused by vacancy collapse induced by severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…Average values of hardness of joint samples in the retreating side are higher than those of the advancing side within HAZ. Similar hardness results were reported by Jia et al [22] and Li et al [23] for FSW aluminium joints. Micro-hardness values of joint samples fabricated by the non-circular pins were found higher than those manufactured by tools with circular pins.…”
Section: Resultssupporting
confidence: 90%
“…Average values of hardness of joint samples in the retreating side are higher than those of the advancing side within HAZ. Similar hardness results were reported by Jia et al [22] and Li et al [23] for FSW aluminium joints. Micro-hardness values of joint samples fabricated by the non-circular pins were found higher than those manufactured by tools with circular pins.…”
Section: Resultssupporting
confidence: 90%
“…Joint samples inside HAZ have an average hardness that is greater on the retreating side than the advancing side. For FSW aluminium joints, similar hardness findings were discovered [22,23]. It was found that joint samples manufactured with non-circular pins had microhardness that was greater than joint samples made with circular pins.…”
Section: Micro-hardnesssupporting
confidence: 64%
“…Thus, researchers need to understand the microstructural evolution and the underlying physics of FSW. For precipitation-hardened Al alloys, such as 6000 and 7000 series, the thermos-mechanical process of FSW results in the change of precipitate structure, size, distribution, and density in different zones [27]. Generally, this change is negative for the strength of the FSW joint.…”
Section: Of 15mentioning
confidence: 99%